Metacognitive Awareness in EFL Reading Comprehension for Senior High School Students: Predictive Insights - Helta Anggia; Kaló Zsuzsa; Kristóf Lakatos; Rafista Deviyanti (FKIP Universitas Lampung, 2026)
Metacognitive awareness is widely recognized as an important factor influencing English as a Foreign Language (EFL) reading comprehension. However, evidence regarding the contributions of its components remains inconclusive, particularly in the Indonesian context. This study examined the relationship between metacognitive awareness and EFL reading comprehension among Indonesian high school students and investigated gender differences in metacognitive awareness. A total of 72 students (42 males and 30 females) participated in the study. Data were collected using the Metacognitive Awareness Inventory (MAI) and a reading comprehension test. The Rasch model implemented in the Quest program was used to analyze item difficulty, and One-Way MANOVA was used to examine gender differences. To investigate the structural relationships between metacognitive awareness dimensions and reading comprehension, Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed. PLS-SEM was selected because it is suitable for exploratory models and can accommodate relatively small samples when model complexity is limited; however, the sample size remains a limitation of the study. The Rasch analysis revealed that items requiring inference of unstated information were the most difficult, whereas vocabulary inference based on contextual clues was the easiest. MANOVA results indicated that female students demonstrated higher levels of metacognitive awareness than male students. The PLS-SEM analysis showed that metacognitive regulation was not significantly associated with reading comprehension. In contrast, metacognitive knowledge exhibited a stronger positive relationship with reading comprehension, suggesting that students’ awareness of their cognitive processes contributes more substantially to reading performance than their regulatory strategies. Although metacognitive regulation did not significantly predict reading performance, metacognitive knowledge emerged as a more meaningful contributor. These results suggest that EFL instruction should place greater emphasis on fostering students’ metacognitive knowledge to enhance reading comprehension. Future research should employ larger and more diverse samples to improve the generalizability of the findings. Keywords: EFL learners, gender differences, metacognitive awareness, metacognitive knowledge, reading comprehension.